Disinfection and decontamination : a practical handbook - Moldenhauer, Jeanne (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book describes various methods of decontamination and how the methods work. There is a discussion of the various cleaning and disinfection methods utilized, along with details of how to qualify these methods. It also describes new technologies that may be useful in the battle for decontamination across industries. Finally, this book provides a single resource on how one can address contamination issues for a variety of manufacturing processes and industries.
Disinfectants and biocides -- Disinfecting agents : "the art of disinfection" -- The microbiome and its usefulness to decontamination/disinfection practices -- Disinfection qualification testing considerations for critical manufacturing environments -- Methods for contamination detection -- Residue removal in cleanroom environments -- Microbiological concerns in non-sterile manufacturing -- Preservatives and why they are useful -- The problem of BCC (Burkholderia cepacia complex) -- What is mold and why is it important for decontamination and disinfection? -- Sterilization methods.
OCLC-licensed vendor bibliographic record.
Keywords: Disinfection and disinfectants -- Technique; Biological decontamination -- Technique; MEDICAL / Forensic Medicine; MEDICAL / Preventive Medicine; MEDICAL / Public Health; MEDICAL / Biotechnology; MEDICAL / Pharmacology; SCIENCE / Biotechnology